2015
DOI: 10.1186/s13148-015-0164-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene-specific DNA methylation profiles and LINE-1 hypomethylation are associated with myocardial infarction risk

Abstract: BackgroundDNA methylation profiles are responsive to environmental stimuli and metabolic shifts. This makes DNA methylation a potential biomarker of environmental-related and lifestyle-driven diseases of adulthood. Therefore, we investigated if white blood cells’ (WBCs) DNA methylation profiles are associated with myocardial infarction (MI) occurrence.Whole-genome DNA methylation was investigated by microarray analysis in 292 MI cases and 292 matched controls from the large prospective Italian European Prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 60 publications
4
63
0
Order By: Relevance
“…A previous study showed that genetic factors are associated with age at stroke onset and sex [47]. Gene-specific DNA methylation profiles and LINE-1 hypomethylation are associated with myocardial infarction risk [48]. Recently, there was an attempt to find predictors of myocardial infarction using genotype/allelic combinations by analysis of genotype frequencies of polymorphic markers [49].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that genetic factors are associated with age at stroke onset and sex [47]. Gene-specific DNA methylation profiles and LINE-1 hypomethylation are associated with myocardial infarction risk [48]. Recently, there was an attempt to find predictors of myocardial infarction using genotype/allelic combinations by analysis of genotype frequencies of polymorphic markers [49].…”
Section: Discussionmentioning
confidence: 99%
“…Guarrera et al found differential methylation of the zinc finger and Broad complex, Tramtrak, Bric à brac (BTB) domain-containing protein 12 ( ZBTB12 ) gene body and LINE-1 hypo-methylation in 291 cases of myocardial infarction vs. 292 controls from a large Italian European Prospective Investigation in to Cancer and Nutrition Study (EPICOR). 51 Replication in a second cohort, demonstrated that including DNA methylation profile with other traditional CVD risk factors may improve risk prediction. 51 CVD has also been associated with DNA methylation changes in response to a number of environmental factors, including air pollution.…”
Section: Health Outcomes and Dna Methylationmentioning
confidence: 99%
“…51 Replication in a second cohort, demonstrated that including DNA methylation profile with other traditional CVD risk factors may improve risk prediction. 51 CVD has also been associated with DNA methylation changes in response to a number of environmental factors, including air pollution. Recently, Zhong et.…”
Section: Health Outcomes and Dna Methylationmentioning
confidence: 99%
“…However, DNA methylation at MTHFR has not been examined to any great extent in relation to hypertension generally. Aberrant LINE-1 and gene-specific DNA methylation profiles have been reported to improve the prediction accuracy of the occurrence of myocardial infarction, when other well-known risk factors for hypertension are taken into account [70]. One randomised controlled trial found that B-vitamin supplementation (folic acid, vitamins B6 and B12) in combination with vitamin D and calcium, increased LINE-1 DNA methylation, but this study did not account for different MTHFR genotypes [71].…”
Section: Biological Mechanisms Linking Blood Pressure With One-carmentioning
confidence: 99%